2004
DOI: 10.1099/vir.0.80345-0
|View full text |Cite
|
Sign up to set email alerts
|

Host-specific encapsidation of a defective RNA 3 of Cucumber mosaic virus

Abstract: Defective (D) RNAs were generated in tobacco upon passage of two isolates of Cucumber mosaic virus (CMV) initially derived from RNA transcripts of cDNA clones. In both cases, the D RNA was derived by a single in-frame deletion of either 339 or 411 nt within the 3a gene of Fny-CMV RNA 3 or M-CMV RNA 3, respectively. The generation of D RNAs was rare and occurred with two CMV isolates, the virions of which were known to differ in physico-chemical properties.The Fny-CMV D RNA 3, designated D RNA 3-1, was maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…It was shown previously that DI RNA was encapsidated (16); however, it may be that the DI particles (or DI RNA) are unable to bind to the necessary virus or host factors required for long-distance movement (11,13). Similar observations were also reported in other studies involving CMV and different hosts as CMV D RNA accumulated in upper leaves of Nicotiana species but did not move systemically in muskmelon, tomato, or zucchini squash (7,8). Therefore, it is also possible that the capacity of DI RNA to move efficiently is host dependent, and the mechanism of inhibition of DI long-distance movement remains to be studied.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It was shown previously that DI RNA was encapsidated (16); however, it may be that the DI particles (or DI RNA) are unable to bind to the necessary virus or host factors required for long-distance movement (11,13). Similar observations were also reported in other studies involving CMV and different hosts as CMV D RNA accumulated in upper leaves of Nicotiana species but did not move systemically in muskmelon, tomato, or zucchini squash (7,8). Therefore, it is also possible that the capacity of DI RNA to move efficiently is host dependent, and the mechanism of inhibition of DI long-distance movement remains to be studied.…”
Section: Discussionsupporting
confidence: 76%
“…Although the DI RNA could represent up to 60% of virusspecific RNA in the infected plants, as in case of tombusviruses, the percentage of encapsidated DI RNAs could be as low as 3 to 4%, and most DI RNAs are not transmitted by vectors (1,2,6). Moreover, while most DI RNAs can efficiently accumulate in inoculated tissue, they do not always move systemically, as exempli-fied by cucumber mosaic virus (CMV) D RNA, which moves long distances in tobacco species but not in tomato, zucchini squash, or muskmelon (1,7,8).…”
mentioning
confidence: 99%
“…Replicase errors and RNA recombination are also responsible for the formation of defective RNAs, the deleted forms of viral RNAs that contain portions of the parental virus genome (21). For instance, the ability of defective RNA to replicate and to interfere with genomic BMV RNA replication has been demonstrated for barley (21,22) and for zucchini (52) protoplasts.…”
Section: Genetic Recombination Of Bromoviridaementioning
confidence: 99%
“…The effect of the plant host on accumulation of D-RNAs has been well documented (Hillman et al, 1987;Graves et al, 1996;Inoue-Nagata et al, 1998;Kaplan et al, 2004). Further, we have recently demonstrated that the host can affect the size of defective RNAs (Llamas et al, 2004).…”
Section: Discussionmentioning
confidence: 99%